Effects of anaerobic training on serum paraoxonase / arylesterase enzyme activities - Turgay, F.; Sisman, A. R.; Cecen Aksu, A.; Akalin, E. (Archivos de medicina del deporte, 2008)
Antioxidant characteristics of high density lipoprotein (HDL) may partly reside on the paraoxonase (PON1) / arylesterase (AE) enzymes it incorporates. Improving effects of aerobic exercise on paraoxonase (PON1) activity and its regulation by PON1-192 polymorphism has documented. The aim of our study is to investigate the effects of anaerobic (judo) training on PON1 / AE activities and its relationship with PON1-192 polimorphism. Methods: A total of 18 Turkish national female judoists (aged 17.9 +/- 0.8 yr) participated in the study. In the 19 week period prior to the competitive season, once at the start and once at the end, serum basal PON1, salt (NaCl) - stimulated PON1 (TSPON1) and AE activities and, PON1 and AE activities in serum HDL and its subfractions (HDL 2 and HDL 3 ) were analysed with kinetic methods. Total cholesterol (TC), HDL-C, HDL 2 -C, HDL 3 -C, LDL-C and triglyceride levels were determined in judoists` fasting venous blood samples, their physical characteristics measured and critical speeds were calculated. PON1-192 polymorphism were determined using TSPON1 / AREST ratio. The phenotype groups were classified as QQ and R carriers (QR+RR). Results: While no significant changes occurred in the players` physical charecteristics and critical speed scores following the training period, significant increases were established in HDL-C and HDL 3 -C levels, serum basal PON1 and AE activities, PON1 activities in serum HDL and its subfractions, and AE activity in HDL. When PON1 polymorphism is concerned, in both Q and R carriers serum basal PON1 and HDL-PON1, in Q group HDL 2 -PON1, in R carrier group HDL 3 -PON1 and HDL 2 -AE activies significantly increased. Triglyceride levels of Q group was more than that of R carriers. Conclusion: Judo training of anaerobic nature may have mediated beneficial effects on HDL-C, PON1 and AE enzyme activities. The differences between the phenotype groups and other group`s results can due to PON1-192 polimorphism.